PENGARUH PROBLEM BASED LEARNING DENGAN STRATEGI PROBING PROMTING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DAN REGULASI DIRI SISWA - Ayu Ardiana; Eka Setyaningsih (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
The purpose of this research is to find: 1). Student's achievement in mathematics communication ability who followed the learning process using Probing Prompting strategy; 2). Student's achievement in self-regulation who followed the learning process using Probing Prompting strategy; 3). Whether a student's achievement in mathematics communication ability who followed the learning process using Probing Prompting strategy is better than a student who followed a direct learning process; 4). Whether a student self-regulation who followed the learning process using Probing Prompting strategy is better than a student who followed a direct learning process.The population of this research is a whole of the 8thgrade students from one of the Junior High School in Purwokerto. The data-gathering process is determined by post-test and questionnaire. The result that can be inferred from the post-test are the class average which using Probing Prompting strategy for their learning process are 72,29 and the class average which using direct learning process are 65,62 and the result that can be inferred from the questionnaire are the class average which using Probing Prompting strategy for their learning process are 76,62 and the class average which using direct learning process are 67,85. The result of this research shows that that student's achievement in mathematics communication ability who followed the learning process using the Probing Prompting strategy is better than a student who followed a direct learning process. Student self-regulation who followed the learning process using the Probing Prompting strategy is better than a student who followed a direct learning process.